(untitled) (Applied Biological Research, 2023)
The aim of present study was to develop an optimum extraction method for high quality edible oil from Symplocos paniculata fruit. S. paniculata fruit oils were extracted by three methods viz., cold pressing (PCP), subcritical extraction (SBE) and Soxhlet extraction (SE). A comparative analysis was performed for their physiochemical properties, fatty acid composition and bioactive substances. The oil extraction rate from SE, SBE and PCP was 36.6, 35.7 and 8.4%, respectively. Total unsaturated fatty acids present were in the range of 79.04-79.35% with 48.13-48.52% oleic acid, and 30.08-30.18% linoleic acid. The ratio of saturated fatty acids to total unsaturated fatty acids was 0.26025 0.2652. PCP extraction oil had the highest content of polyunsaturated fatty acids, while SBE extracted oil had highest content of unsaturated fatty acids, along with rich bioactive substances. Based on the criterion of extraction rate, oil composition and bioactive substances, the SBE method appeared optimum method for extracting high quality edible oil from S. paniculata fruits.